Jurnal Perencanaan Karir dan Pengembangan Profesional Perawat - Prabowo, Budi; Samsudin, Acep; Syahputra, Rizky Tri; Dibba, Farah; Safitri, Rifasya Safira (Jurnal Ilmiah Wahana Pendidikan, 2024)
Career and Professional Development are key elements in providing quality health care to patients, including those who are older and living in multiple care settings. This article reviews the importance of career planning and professional development for nurses based on the changing health care landscape. Key factors that support career planning and professional development for nurses include access to structured learning, a supportive work environment, leadership development, and career resilience. In addition, integrated career development programs in nursing curricula can have a positive impact on nursing students’ career resilience. In addition, there are differences in career planning practices between private and public hospitals, with career development practices being more sophisticated in private hospitals. This underscores the importance of career planning in nursing care and the role of nurse managers in nurses’ career development.